Innovative Perspective of Marketing Engagement: Enhancing Users’ Loyalty in Social Media through Blogging - Muhammad Sajjad; Umer Zaman (Journal of Open Innovation: Technology, Market and Complexity, 2020)
The breakneck pace of digital technologies has created a dramatic shift in marketing campaigns to engage users through unique and innovative experiences. Focusing on the same grounds, this study relates the market engagement with users’ loyalty (UL) for Facebook social media. Market engagement has been measured through four constructs of innovative engagement (IE), functional engagement (FE), emotional engagement (EE), and communal engagement (CE). Blogging has been included as a moderator in the relation between IE, FE, EE, CE, and UL. To measure these relationships, study proposed two models and developed five hypotheses. Data were collected through structured questionnaire aimed at referral groups i.e., habitual users of Facebook. A total of 309 responses were included in the analysis through purposive sampling. Model 1 was tested with simple regression and it was found that the overall model was statistically significant and explained 65 percent of variation in UL. It was concluded that for online users, loyalty is affected by IE, FE, and CE, while EE is of least concern for them. Model 2 was tested through hierarchical regression after the inclusion of a moderator of BE in model 1. It was concluded that blogging acted as a partial moderator in between the relationship of IE, FE, EE, CE, and UL as the proposed model 2 was found to be significant. However, only CE yielded significant relationship with UL while IE, FE, and EE yielded insignificant relationship with UL in the presence of a moderator. The study concedes new insights for those social platforms and marketing companies that are seeking innovative and unique ways to retain their online users for long time.